2019
DOI: 10.1038/s41598-019-46772-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-aminolevulinic acid and sodium ferrous citrate on fibroblasts from individuals with mitochondrial diseases

Abstract: Mitochondrial respiratory chain complexes II, III, and IV and cytochrome c contain haem, which is generated by the insertion of Fe 2+ into protoporphyrin IX. 5-Aminolevulinic acid (ALA) combined with sodium ferrous citrate (SFC) was reported to enhance haem production, leading to respiratory complex and haem oxygenase-1 (HO-1) upregulation. Here, we investigated the effects of different concentrations of ALA and SFC alone or in combination (ALA/SFC) on fibroblasts from 8 individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Recently, it has been reported that 5-aminolevulinic acid and sodium ferrous citrate improved mitochondrial functions in skin fibroblasts from patients with mitochondrial diseases, which may become a new treatment option for mitochondrial diseases. 25 In our case, as the symptoms gradually worsened and there were no other specific treatment, we initiated 5-aminolevulinic acid as a treatment, which decreased frequency of seizures. Long-term follow-up is necessary to evaluate the efficacy of 5-aminolevulinic acid.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, it has been reported that 5-aminolevulinic acid and sodium ferrous citrate improved mitochondrial functions in skin fibroblasts from patients with mitochondrial diseases, which may become a new treatment option for mitochondrial diseases. 25 In our case, as the symptoms gradually worsened and there were no other specific treatment, we initiated 5-aminolevulinic acid as a treatment, which decreased frequency of seizures. Long-term follow-up is necessary to evaluate the efficacy of 5-aminolevulinic acid.…”
Section: Discussionmentioning
confidence: 74%
“…In present study, addition of 5-ALA significantly increased the sperm mitochondrial membrane depolarization ( Figure 1A–B ) maybe because the sperm utilizes 5-ALA to synthesise heme. It was supported by Shimura et al [ 29 ] who observed that 5-ALA upregulated oxidative phosphorylation proteins with increased oxidative phosphorylation gene expression in human skin fibroblasts. The result also agreed with the observation that 5-ALA was necessary to produce heme proteins [ 26 , 30 32 ].…”
Section: Discussionmentioning
confidence: 75%
“…[ 6 ] In addition, Shimura et al recently reported that 5-ALA/SFC increased the oxygen consumption rate and ATP level via an oxidative phosphorylation protein's expression induced by upregulations of heme, heme oxygenase-1, and the mtDNA copy number in skin fibroblasts from individuals with mitochondrial disease. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%